Screening of antibacterial activity from biosynthesized silver nanoparticles using Diospyros discolor Willd. extract. Issue 1 (March 2020) - Rahim, L; Handayani, W; Santoso, I; Imawan, C
Abstract: Silver nanoparticles (AgNPs) have a specific property for antibacterial agents. This research aims to explore the antibacterial activity from the AgNPs synthesized using Diospyros discolor Willd. extract. We determined that the leaf extract solution of D. discolor can provide reducing properties for AgNPs synthesis. The result showed a maximum absorbance peak wavelength between 420–450 nm in the produced AgNPs. The Transmission Electron Microscope (TEM) image supported the presence of AgNPs, with size between 10–50 nm. Antimicrobial assays using E. coli produced an inhibition zone of 7.4 ± 0.7 mm from the centrifuged AgNPs, whereas those using S. aureus produced an inhibition zone of 7.66 ± 0.9 mm. An antimicrobial activity index (AI) assay against E. coli resulted in 0.2 ± 0.1 mm, whereas the activity against S. aureus resulted in an activity index of 0.40 ± 0.19 mm. AI values that were lower than 1.0 was considered had less significant activity. We also tested the growth of bacteria in the medium added with AgNPs using the dilution method. The growth of bacteria colony from the streak line showed a decline in growth for the bacteria that had been exposed to biosynthesized AgNPs with the increasing of time exposure for 5, 10 and 15 minutes, respectively.